The contribution of cis- and trans-acting variants to gene regulation in wild and domesticated barley under cold stress and control conditions. (28th January 2020) - Haas, Matthew; Himmelbach, Axel; Mascher, Martin
Abstract: Barley, like other crops, has experienced a series of genetic changes that have impacted its architecture and growth habit to suit the needs of humans, termed the domestication syndrome. Domestication also resulted in a concomitant bottleneck that reduced sequence diversity in genes and regulatory regions. Little is known about regulatory changes resulting from domestication in barley. We used RNA sequencing to examine allele-specific expression in hybrids between wild and domesticated barley. Our results show that most genes have conserved regulation. In contrast to studies of allele-specific expression in interspecific hybrids, we find almost a complete absence of trans effects. We also find that cis regulation is largely stable in response to short-term cold stress. Our study has practical implications for crop improvement using wild relatives. Genes regulated in cis are more likely to be expressed in a new genetic background at the same level as in their native background. Abstract : We present evidence for a near absence of trans effects controlling gene regulation in response to domestication and environmental stress